Bridging Service Quality Gaps in Hospital Nutrition Service: An Integrated SERVQUAL and Kano Model Analysis - Hera Laxmi Devi Septiani; Shofia Salsabila; Henry M.P. Siahaan (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Hospital nutrition services support patient recovery and healthcare quality; however, unmet service attributes still cause dissatisfaction. Although service quality has been widely studied, the integration of SERVQUAL and the Kano Model for evaluating hospital nutrition services remains limited. Objective: This study aimed to assess patient satisfaction with hospital nutrition services in West Java by applying an integrated SERVQUAL and Kano Model approach to identify service quality gaps and prioritize areas for improvement. Methods: A cross-sectional quantitative study with a descriptive-analytical design was conducted involving 99 hospitalized patients receiving nutrition services at a hospital in West Java. Participants were selected using purposive sampling and had received nutrition services for at least two days. Data were collected using SERVQUAL and Kano Model questionnaires. SERVQUAL analysis measured the gap between patients' perceptions and expectations across five service quality dimensions, while the Kano Model classified service attributes according to their influence on patient satisfaction. Results: All SERVQUAL dimensions showed negative gap scores, indicating that patients' expectations exceeded their perceptions of the nutrition service. The largest gaps were observed in the assurance (Gap = −0.90), responsiveness (Gap = −0.88), and empathy (Gap = −0.87) dimensions, suggesting that these areas should be prioritized for service quality improvement. Kano analysis revealed that most service attributes were classified as attractive and one-dimensional, indicating that improvements in menu quality, food presentation, staff friendliness, and service responsiveness have the greatest potential to enhance patient satisfaction. Conclusion: The integration of SERVQUAL and the Kano Model effectively identifies priority areas for enhancing hospital nutrition services, particularly in the reliability and responsiveness dimensions. This integrated approach provides a systematic framework for improving service quality based on patient expectations and satisfaction determinants.